LIVELIHOOD NELAYAN TRADISIONAL DANAU SINGKARAK NAGARI GUGUAK MALALO KECAMATAN BATIPUH SELATAN KABUPATEN TANAH DATAR - Roza Oktavia; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study analyzed the livelihood of traditional fishermen of Lake Singkarak Guguak Malalo village. Traditional fishermen who only uses a paddle boat for fishing can’t compete with modern fishermen who use fishing gear motor boat and chart (floating net). The state of fishermen in this village is very concern their low income due to technological limitations, limited education and no capital. This makes them not able to move the livelihood of other subjects that can guarantee their livelihood. The theory used is the theory subsistence according to James C. Scott. The data Analysis is done by means of descriptive qualitative, data collection techniques in this study is pourposive where the number of respondents amounted to 6 people consisting of 4 men and 2 women. From the research field that the livelihood of traditional fisherman who ude Lake singkarak Nagari Guguak Malalo village is to have a second job (Daily Labour), savings, and debt. Then the fishing grounds remain the traditional fishermen is due lack of education, did not venture out of the village and the system looks for fish that have been passed on for generations.Keywords: livelihood, traditional fishermen